2015
DOI: 10.3892/or.2015.4248
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous hydrogen sulfide promotes C6 glioma cell growth through activation of the p38 MAPK/ERK1/2-COX-2 pathways

Abstract: Abstract. Hydrogen sulfide (H 2 S) participates in multifarious physiological and pathophysiologic progresses of cancer both in vitro and in vivo.We have previously demonstrated that exogenous H 2 S promoted liver cancer cells proliferation/anti-apoptosis/angiogenesis/migration effects via amplifying the activation of NF-κB pathway. However, the effects of H 2 S on cancer cell proliferation and apoptosis are controversial and remain unclear in C6 glioma cells. The present study investigated the effects of exog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Several lines of studies show that exogenously administered or endogenously produced H 2 S can induce pro-proliferative signaling pathways (including MAP kinases, Akt, ERK1 activation) (5)(6)(7)(35)(36)(37)(38)(39)(40)(41)(42)(43). By inhibiting colon cancer cell H 2 S production, YD0171 may suppress these signaling processes, although this remains to be directly investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of studies show that exogenously administered or endogenously produced H 2 S can induce pro-proliferative signaling pathways (including MAP kinases, Akt, ERK1 activation) (5)(6)(7)(35)(36)(37)(38)(39)(40)(41)(42)(43). By inhibiting colon cancer cell H 2 S production, YD0171 may suppress these signaling processes, although this remains to be directly investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S enhances the supply of nutrients and blood to the tumor cells and tissues (29). Our latest research also showed that exogenous H 2 S promoted cancer cell proliferation/antiapoptosis/angiogenesis/migration effects via amplifying the activation of NF-κB (30) and p38 MAPK/ERK1/2-COX-2 pathways (31). However, research focused on the effect of exogenous H 2 S on esophageal EC109 cells and its potential mechanisms is lacking.…”
Section: Exogenous Hydrogen Sulfide Exerts Proliferation Anti-apoptomentioning
confidence: 99%
“…This indicates that exogenous H 2 S can activate the STAT3 and COX-2 signaling pathways in PLC/PRF/5 cells. Previous studies have shown that the STAT3 (13-17) and COX-2 (32,(43)(44)(45) signaling pathways are associated with tumorigenesis. The present study hypothesized that the STAT3 and COX-2 signaling pathways may be involved in the effects of exogenous H 2 S on the growth of PLC/PRF/5 cells.…”
Section: The Stat3-cox-2 Signaling Pathway Participates In Nahs-inducmentioning
confidence: 99%
“…H 2 S can protect cancer cells from chemopreventive agent β-phenylethyl isothiocyanate-induced apoptosis (30) and promote proliferation (30), which may be mediated by the increase in Akt and extracellular signal-regulated kinase (ERK) phosphorylation, and the decrease in p21 Waf1/Cip1 expression and NO production. A recent study by our group revealed that exogenous H 2 S promotes C6 glioma cell growth through the activation of the p38 MAPK/ERK1/2-COX-2 signaling pathway (32). Furthermore, in PLC/PRF/5 cells, exogenous H 2 S exerts proliferation, anti-apoptosis, angiogenesis and migration effects via amplifying the activation of the nuclear factor (NF)-κB signaling pathway (24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation